Evaluation of undergraduate business education programme in universities in South-West, Nigeria (2019)
The study examined the challenges facing the business education, availability of facilities and equipment for teaching business education and comparisons of content taught and content objective of business education in universities in south west, Nigeria. Stratified random sampling was used in selecting 417 respondents, out of which 59 were lecturers, 19 technical-instructors, 179 undergraduate business education students, 80 employed business education graduates and 80 employers of business education graduates. Three major structured research instruments were used in this study for collection of data, they are: Business Education Programme Problem Check List with reliability r = 0.97, Attainment of Business Education Programme Objective Inventory with reliability coefficient r = 0.97 and Facilities, Equipment and Resources Inventory with reliability coefficient of r = 0.90. Three research questions were raised and answered using frequency counts and percentages. Results indicated that both the contents of the Business education programmes taught and the contents specified in the objectives of the programmes are comparable. Facilities, equipment and resources meant for business were not adequate and accessible in south west universities and that finally, business education programme‟s faces various challenges such as inadequate infrastructural and instructional facilities, lack of state policy statement on business education programme and etc. Hence it is recommended that the teachers should expose their learners to practical aspect of business education that will enable them stand on their own after graduation. The government should address the problem associated with business education programme.